2013
DOI: 10.4161/pri.23711
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquilin-1 and protein quality control in Alzheimer disease

Abstract: Single nucleotide polymorphisms in the ubiquilin-1 gene may confer risk for late-onset Alzheimer disease (AD). We have shown previously that ubiquilin-1 functions as a molecular chaperone for the amyloid precursor protein (APP) and that protein levels of ubiquilin-1 are decreased in the brains of AD patients. We have recently found that ubiquilin-1 regulates APP trafficking and subsequent secretase processing by stimulating non-degradative ubiquitination of a single lysine residue in the cytosolic domain of AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 57 publications
(70 reference statements)
0
21
0
Order By: Relevance
“…The level of ubiquilin-1 is decreased in both DS and DS/AD compared with their respective age-matched controls and we observed a decreased of K63 poly-Ub levels. Single-nucleotide polymorphisms in the ubiquilin-1 gene are likely a risk factor for late-onset AD (20). Stieren et al demonstrated that overexpression of ubiquilin-1 reduces the Ab 42/40 ratio and prevents APP-induced cellular toxicity (67).…”
Section: Discussionmentioning
confidence: 99%
“…The level of ubiquilin-1 is decreased in both DS and DS/AD compared with their respective age-matched controls and we observed a decreased of K63 poly-Ub levels. Single-nucleotide polymorphisms in the ubiquilin-1 gene are likely a risk factor for late-onset AD (20). Stieren et al demonstrated that overexpression of ubiquilin-1 reduces the Ab 42/40 ratio and prevents APP-induced cellular toxicity (67).…”
Section: Discussionmentioning
confidence: 99%
“…Among the five ubiquilin proteins, Ubqln1, Ubqln2 and Ubqln4 have been found in all tissues, whereas Ubqln3 and Ubqlnl appear to be enriched in testis (http://www.proteinatlas.org/). In comparison, Ubqln1 and Ubqln2 have the highest levels of expression among all ubiquilin genes in most mouse and human tissues (15), and have been implicated in several neurodegenerative disorders (15,57,58). Therefore, we have selected these two ubiquilins for this work.…”
Section: Developing a New Dual-bait Strategy For Effective Isolation mentioning
confidence: 99%
“…12 Chaperones are constitutively expressed in eukaryotes along with co-chaperones (proteins that facilitate the function of chaperones in protein folding but are not able to do so by themselves only). 8 These chaperones undergo various modifications during cellular stress such as glycosylation, phosphorylation, and 2 …”
Section: Chaperones and Protein Homeostasismentioning
confidence: 99%
“…7 Thus, understanding the proteostasis machinery both within and outside the cells is of importance. A detailed role of heat shock proteins (HSPs), ubiquilin-1, 8 and other intracellular chaperones in proteostasis has been reviewed in detail elsewhere. 9 Here, in this review article, the focus is on the protein quality control at the extracellular space and the abundance of the extracellular chaperones (ECs) in this space on exposure to different stressors such as temperature, pH, oxidised microenvironment, and the shear stress arising from the flow of plasma throughout the body under certain pressure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation